Effectiveness of exercise program on abdominal muscular endurance and 20 meters running speed during covid-19 pandemic - Syeni Ratna Amelia; Achmad Sofyan Hanif; Fatah Nurdin; Hernawan Hermawan; Firdaus Hendry Prabowo Yudho (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2022)
This study aims to reveal the significance of changes in the abilities of athletic athletes at the Student Sports Training Center in the Special Capital Region of Jakarta. The study was carried out during the pandemic for 5 months with a quantitative approach, descriptive and inferential analysis was carried out using the normality test method and the paired sample T-Test significance test. The results showed normal research data with no significant relationship between abdominal muscular endurance variables and 20m running speed physical test results after and before the treatment was carried out. The results of the paired sample T-test showed no significant correlation between the variables studied, with the results of the calculation of paired sample correlations p=0.194 on sit-ups 1 and 2 data, and p=0.083 for 20m running speed data at a significance level of =0.05. The results of the paired sample test showed that there was no significant difference between the abdominal strength variables and the 20m running speed, with the data showing p= 0.28 for the sit-ups T-test results and p=0501 for the paired 20m running speed T-test results at =0.05.